The Single Transferable Vote and the Alliance Party of Northern Ireland. Issue 4 (1st October 2016) - Jarrett, Henry
Abstract : This article assesses the operational challenges faced by the non-sectarian Alliance Party of Northern Ireland and seeks to determine whether use of the PR-STV voting system has a negative electoral impact on the party. It argues that whilst PR-STV is favourable to small parties as it allows inter-party lower order preference votes (or transfers) to be cast, it is of limited benefit to Alliance. This is due to most unionist and nationalist party first preference voters making only intra-bloc transfers, which disadvantages Alliance as it is the only significant non-sectarian party in Northern Ireland. Furthermore, for Alliance to encourage its first preference voters to transfer to an ethno-national party in the hope that this advice is reciprocated would go against its staunchly non-sectarian position. The party does not, therefore, benefit from PR-STV to the extent that many ethno-national parties do. Non-sectarian parties are, however, a product of ethnic party systems. In deeply divided societies dominated by ethno-national parties, PR-STV at least has the potential for these to moderate towards the centre ground in an attempt to acquire transfers from the widest possible audience. This article does not, therefore, recommend the implementation of an alternative electoral system in Northern Ireland.